SOURCES OF INCOME INEQUALITY AND EQUITY: A STUDY IN TRIBAL AREAS OF TAMIL NADU - Meganathan, N; Selvakumar, K N; Prabu, M; Pandian, A Serma Saravana; Kumar , G Senthil (Indian Journal of Veterinary Sciences and Biotechnology, 2009)
A study was undertaken to identify the role of livestock as the income stabilising source among the tribal farmers of Tamil Nadu by collecting data from the 900 sample tibal farmers of six hilly areas of Tamil Nadu . The data were analysed by using Gini concentration ratio and depicting Lorenz curve . The results revealed that the income inequality was very high in crop enterprises (Gini ratio 0.69 ) followed by non farm income ( 0.49) and livestock income ( 0.39) with the overall inocme inequality of 0.39 . The income from livestock source was more evenly distributed than the other sources: the Gini coefficient of non-farm activity was found to be the least (0.09) in Kolli hills and the highest in Yelagiri hills (0.64). Among the three activities, livestock income was equally distributed more in Kolli hills (0.19) followed by Yercaud hills (0.26), Sitheri hill (0.36), Ooty hill (0.41) and last equally distributed in Yelagiri hills (0.43). The study revealed that the livestock rearing reduces the income disparities among the tribal households. As the livestock sector provides stable income compared to crop, measures may be initiated to involve the tribal farmers in livestock farming while framing policies and strategies for poverty alleviation programme in tribal areas of Tamil Nadu.